The importance of biodiversity conservation as a factor of ecotourism development at the Goc mountain - Kostić, Marija; Petrović, Milica (Hotel and Tourism Management, 2013)
The Republic of Serbia as part of the Balkan Peninsula is an area with a high level of biological diversity, especially in mountain regions. The concept of sustainable use of biodiversity, in terms of its conservation, is a model that can strongly contribute to the development of rural highland areas of the country. Forest resources, beside to the potential of biomass production, are a key resource for the promotion of different forms of tourism. Farming and production, in mountain areas, should be focused on the native, indigenous varieties and traditional species, and there are proper opportunities for growing some medicinal herbs. In addition, missing infrastructure, lack of investment and subsidies, as well as depopulation, the problem of promoting sustainable use of biodiversity also lay in lack of regional and local development strategies, lack of education and low level of public awareness about value and potential of our biological resources. Mentioned in this paper are qualitative and quantitative features of biodiversity at the mountain Goc in order to preserve and protect the environment on the one hand, and to examine the possibilities and lay the basis for the tourism development of special interests on the other.